Schnitzler's century: The making of middle-class culture 1815-1914 - Gay, Peter (New York W. W. Norton & Company, 2002)
This is cultural history of the first order, and it is liberal and humane history at its very best."?David CannadineAn essential work for anyone who wishes to understand the social history of the nineteenth century, Schnitzler's Century is the culmination of Peter Gay's thirty-five years of scholarship on bourgeois culture and society. Using Arthur Schnitzler, the sexually emboldened Viennese playwright, as his master of ceremonies, Gay offers a brilliant reexamination of the hundred-year period that began with the defeat of Napoleon and concluded with the conflagration of 1914. This is a defining work by one of America's greatest historians. 12 b/w illustrations.Show More Show Less --------------------------------------------------------------------------------